The pediatric airway : cry, stridor, and cough - Illényi, András; Koltai, Peter J.; Szende, Tamás; Hirschberg, J.; Hirschberg, J. (Plural Publishing Inc., 2015)
This multidisciplinary book describes 42 different pathological sounds, occurring in different combinations, in 54 different pathological conditions. Uniquely, while recognizing the indispensability of conventional investigation methods - endoscopy, radiology, MRI - the editors demonstrate the value of perceptive-auditive evaluation and objective acoustic analysis as a complimentary diagnostic tool. A major feature of the book is that the diagnostic evaluations are based on exactly determined parameters in terms of acoustics.